Characterization of liver oils from three species of sharks collected in Tunisian coasts: In vitro digestibility by pancreatic lipase. Issue 1 (24th October 2017) - Achouri, Neila; Smichi, Nabil; Kharrat, Nadia; Rmili, Fatma; Gargouri, Youssef; Miled, Nabil; Fendri, Ahmed
Abstract: The increase in world fish lipid request has made necessary the search for new fish species rich in polyunsaturated fatty acid (PUFA) that could be used as raw material for oil production. In this study, liver oils from the deep‐sea sharks Mustelus mustelus, Squalus acanthias, and Rhinobatos cemiculus were extracted and analyzed to describe their lipids characteristics. Lipid contents of shark livers ranged from 64.245 to 69.57%. Among minerals, potassium and sodium were the most abundant while unsaturated fatty acids (FAs) were dominant exceeding 55% of the total FAs. Omega‐3 PUFA (ω‐3 PUFA) profiles exhibited a dominance of eicosapentaenoic acid and docosahexaenoic acid. This study suggests that shark livers, actually considered as waste, may be an attractive source of ω‐3 PUFAs and a good source of carotenoids and phenolic compounds. Practical applications: The production of EPA and DHA concentrates from residual sources of marine oils has unexplored potential of use in food industry and oil‐based nutraceutical production for obtaining health benefits can be achieved. The economic activities of fish residues can reduce inappropriate excessive fishing, reducing imports of fish oils while contributing to the ecosystem balance.